2023
DOI: 10.3390/ijms24087630
|View full text |Cite
|
Sign up to set email alerts
|

A Concerted Vision to Advance the Knowledge of Diabetes Mellitus Related to Immune Checkpoint Inhibitors

Abstract: The rubric of immune-related (ir) diabetes mellitus (DM) (irDM) encompasses various hyperglycemic disorders related to immune checkpoint inhibitors (ICPis). Beyond sharing similarities with conventional DM, irDM is a distinct, yet important, entity. The present narrative review provides a comprehensive overview of the literature regarding irDM published in major databases from January 2018 until January 2023. Initially considered rare, irDM is increasingly being reported. To advance the knowledge of irDM, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 157 publications
0
1
0
Order By: Relevance
“…de Filette et al ( 44 ) reported that at least one of the islet autoantibodies was positive in 53% of patients with TIDM and 15% of them had at least two positive autoantibodies. However, the association between islet autoantibodies and diagnosis of ICI-DM remains unclear ( 45 ). In the case series reported in the present study, ICA in case 1 was positive for DKA, while GADA was positive in case 2 and the patient from case 3 was negative for autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…de Filette et al ( 44 ) reported that at least one of the islet autoantibodies was positive in 53% of patients with TIDM and 15% of them had at least two positive autoantibodies. However, the association between islet autoantibodies and diagnosis of ICI-DM remains unclear ( 45 ). In the case series reported in the present study, ICA in case 1 was positive for DKA, while GADA was positive in case 2 and the patient from case 3 was negative for autoantibodies.…”
Section: Discussionmentioning
confidence: 99%